Influence of chronic ischemic disorders in the prostate on the development of benign prostatic hyperplasia - G. E. Roitberg; K. G. Mkrtchyan; N. G. Kulchenko (Исследования и практика в медицине, 2020)
Purpose of the study. To assess the degree of influence of ischemic disorders in the prostate on the level of androgens.Materials and methods. This was an experimental study that included 20 white non-linear sexually Mature rats. All animals were divided into 2 equal groups: main and control (intact). In the main group of animals (n=10), we created a model of chronic ischemic disorders in the prostate by partial ligation of the inferior Vena cava. After 1.5 months, we conducted a hormonal study in all rats (n=20) — determining the concentration of androgens (testosterone, dihydrotestosterone) and estrogens (estradiol) in the blood of animals and prostate tissue.Results. In the blood of animals of both groups, the level of total testosterone and estradiol did not significantly differ (p>0.05). The level of dihydrotestosterone in the blood serum of rats of the main group on the background of ischemia was reduced by 18.1%, compared to the intact group (p>0.05). However, we detected elevated levels of testosterone (p<0.05) and dihydrotestosterone (p>0.05) in prostate tissue against the background of chronic ischemia.Conclusions. Chronic ischemic disorders in the prostate can be an independent pathogenetic factor in the development of BPH. Vascular damage leads to impaired blood flow and hypoxia, with increased tissue concentration of testosterone, which potentiates the development of BPH.